Syngas software for biomass gasification process - Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (IOP Publishing Ltd, 2019)
In this work, the thermodynamic equilibrium model has been developed in Excel software for evaluating gasification process. The software is called as Syngas software is applicable to study the effects of gasification temperature either using air or steam as gasifying agents for a wide range of biomass. The application of Syngas software has been highlighted through gasification of EFB using air as gasifying agents. The effects of gasification temperature between 650°C and 900°C has been conducted. The highest amount of hydrogen gas and carbon monoxide gas produced are 29.4 mol% and 44.1 mol% respectively at gasification temperature of 900°C. Meanwhile around 19.5 mol% of carbon dioxide gas and 5.8 mol% of methane gas have been generated at similar gasification temperature. The thermodynamic equilibrium model developed in the Syngas software has been validated against experimental data where root mean square errors (RMSEs) lesser than 1 is obtained indicating a reliable of the developed Syngas software.